KEPATUHAN REGULASI, CHARTER VALUE, LDR, UKURAN TERHADAP RISIKO KREDIT PERBANKAN - Susanto, Deddy (Students Journal of Economic and Management, 2012)
This research is to examines the impact of the regulation, the charter value, loan to deposit ratio and bank size on banking credit risk. By using a sample of commercial banks operating in Indonesia and performed testing with ordinary least square (OLS) model, the result obtained was that the charter value negatively affected the level of credit risk. This finding indicates that the low charter valueÂ provides a strong incentive for the occurrence of moral hazard than when the bank has a high charter value.Â Regulation had positive effect on the credit risk. This finding was consistent with the entrenchment argument. In this case, with increasing regulatory compliance, the shareholder take the risk investments to get higher returns as compensation for the loss of utility to comply the regulations. Loan to deposit ratio had positive effect on credit risk. It shows that asymmetric information creates adverse-selection problems. Bank size had positive effect on credit risk. Small banks have more risk inherent in their loan portfolio because they cannot diversify as well as large bank. Small banks, however, do make loans with less credit risk than large banks. Keywords: regulation, charter value, loan to deposit ratio, bank size, credit risk, moral hazard, asymmetric information